Um Estudo Exploratório sobre Plataformas Digitais para Ecossistemas de Inovação Social no Brasil - Chueri, Luciana; Afonso, Anderson; Pinheiro, Mariana; Ramos, Mateus Lambranho; dos Santos, Rodrigo Pereira (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2020)
Due to the growing need for allowing different social innovation project actors to work in a coordinated and collaborative manner, the use of digital platforms has been considered as a great opportunity for social innovation ecosystems. However, in addition to technical issues, the existing challenges in the design and management of such platforms are combined with economic and social issues. This paper presents an exploratory study on real social innovation platforms to investigate technical, human and organizational factors. We expected that this study stimulates researchers and professionals to better design and manage such platforms in the context of social innovation.